Benefícios da ludoterapia como cuidado paliativo em crianças hospitalizadas com câncer - Silva, Flor de Maria Araujo Mendonça (2009)
Introduction: The symbolic meaning of negative aspects carried on the hospitalization and how the play therapy could be an alternative of expression for the child to elaborate emotional and traumatic aspects resultant of the hospitalization. Objectives: The general objective of this research was to analyze the psychological benefits produced by the play therapy as a palliative care on the hospitalized children with cancer. The specific objectives were to evaluate through the HTP projective test on its chromatic form, the importance of the play therapy as a palliative care for the hospitalized children with cancer, to identify the emotional conditions of children with cancer and how they catch it, to evaluate the benefits that the symbolic representations made during serious and/or terminal chronic disease produce on the children. Methodology: On this research, it has worked aspects linked with behavioral, social, psychic defenses and somatic disturbances conditions, through the play therapy with hospitalized children, as well as emotional and psychological-affective aspects involved on the diseasing. The samples of the research were 10 male and female children, from 5 to 12 years old, hospitalized because of the cancer disease. This is a quantitative research with an experimental analytic frame (conjugate), clinical and not randomized assay lineation and exploratory and descriptive research as well. In order to analyze the psychological benefits of the play therapy as a palliative care on the hospitalized children due to a cancer, two psychological evaluations with the children were performed, one before starting this intervention process and another at the end of it. Thus, the results of both evaluations were compared. The quantitative attributes were analyzed by the statistic program SPSS for Windows 16.0 (2007). The statistic descriptive analysis was performed by the Signs Test, comparing the attribute in two times (before and after). The values of p < 0,05 were considered significant. The basis of the information were hospital papers (medical dossier), anamnesis with parents or caretaking, biased observation of the behavioral and social attributes, psychic defenses and somatic disturbances by application of the projective test and by the quantitative and qualitative evaluation of HTP on the chromatic form; semi-structured interview with the children under the HTP pattern. Results: The results about behavioral, social, psychic defenses and somatic disturbances attributes evaluated during the play therapy process with hospitalized children with cancer, standard to: p=0.508; p=0.754; p=0.016; e, o p=1. Final Considerations: This research has showed the benefits produced by the play therapy as a palliative care to hospitalized children with cancer, although the quantitative results on the behavioral, social and psychic attributes has not shown significance, it was evident that a significant number of attributes has maintained stable, even not having remissibility of the symptoms at the end of the play therapy process. The fact of not having negative evolution of some present symptoms, the stability forwarded can be seen as a meaningful positive result of the play therapy and could be an instrument with potentiality functions for the hospitalized children.